2021
DOI: 10.2147/jbm.s288634
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Acquired Factor XIII Deficiency: A Case Report

Abstract: Autoimmune acquired factor XIII (FXIII) deficiency is a rare disorder characterized by severe spontaneous hematomas and autoantibodies against FXIII. High mortality rates have been reported (18% within a year of diagnosis). We present a 70-year-old patient with recurrent muscular hematomas. The basic hemostasis study and the coagulation factors were within normal ranges. The aggregation platelet study was also normal and von Willebrand disease was excluded. Bearing in mind the recurrent bleeding history and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this second case, immunosuppressive therapy was halted before FXIII activity was improved because of her age and low activity of daily life. Another case report also showed discontinuation of standard aggressive immunotherapy owing to adverse effects in a 70-year-old man [19]. Therefore, after acute bleeding is controlled, if the possibility of life-threatening bleeding (e.g., intracranial, intraabdominal, or intrathoracic bleeding) is appropriately explained and the patient agrees that their activity should be restricted, conservative management alone could be a reasonable option.…”
Section: Discussionmentioning
confidence: 99%
“…In this second case, immunosuppressive therapy was halted before FXIII activity was improved because of her age and low activity of daily life. Another case report also showed discontinuation of standard aggressive immunotherapy owing to adverse effects in a 70-year-old man [19]. Therefore, after acute bleeding is controlled, if the possibility of life-threatening bleeding (e.g., intracranial, intraabdominal, or intrathoracic bleeding) is appropriately explained and the patient agrees that their activity should be restricted, conservative management alone could be a reasonable option.…”
Section: Discussionmentioning
confidence: 99%
“…This acquired factor XIII deficiency can be classified as immune mediated due to autoimmune diseases and nonimmune mediated including increased consumption or reduced production like recent surgery, liver disease, malignancy, sepsis, or drug induced (Isoniazid, phenytoin, penicillin, ciprofloxacin and procainamide). Rarely it can occur due to inhibitor development against factor XIII in inherited deficiency patients receiving factor replacement therapy and can cause severe bleeding (2). Recently it was found that COVID -19 is also associated with acquired factor XIII deficiency (4).…”
Section: Case Presentationmentioning
confidence: 99%